Effect of Face Masks on Interpersonal Communication During the COVID-19 Pandemic - Mheidly, Nour; Fares, Mohamad Y.; Zalzale, Hussein; Fares, Jawad (Frontiers in Public Health, 2020)
Interpersonal communication has been severely affected during the COVID-19 pandemic. Protective measures, such as social distancing and face masks, are essential to mitigate efforts against the virus, but pose challenges on daily face-to-face communication. Face masks, particularly, muffle sounds and cover facial expressions that ease comprehension during live communication. Here, we explore the role of facial expressions in communication and we highlight how the face mask can hinder interpersonal connection. In addition, we offer coping strategies and skills that can ease communication with face masks as we navigate the current and any future pandemic.